Children Perception of 3D Usual Shapes in Virtual Environments (Journal of Education and Development, 2023)
Improving the understanding of the 3D perception spatial ability for children is an important issue for research in the areas of cognitive and developmental psychology, particularly in virtual environments where perceptive behaviors could differ from real environment. The aim of this research is to evaluate if children from 6 to 10 years old are able to perceive usual 3D shapes displayed in virtual environment like in 3D world. In an experimentation, children (N =218) are split in groups faced with different modalities of representation of 3D shapes they are allowed to manipulate or only observe: virtual representations on touchpad or real representation with 3D models. They have to solve recognition task of usual 3D shapes (cube, cylinder, triangular prism, etc.). If results indicate that majority of children adequately perceived virtual usual 3D shapes, this ability is not acquired for everyone and is more problematic than perception of 3D models. Some shapes, like the triangular prism, were less adequately perceived. Results call for prudence regarding the use of virtual 3D shapes with children for example during 3D geometry learning.